Identification of fused bicyclic derivatives of pyrrolidine and imidazolidinone as dengue virus-2 NS2B-NS3 protease inhibitors - Weng, Zhibing; Graf, Dominik Korbinian; Klein, Christian D. (European journal of medicinal chemistry, 2017)
A series of fused ring derivatives of pyrrolidine and imidazolidinone were designed, synthesized, characterized and assayed against the DENV-2 NS2B-NS3 protease and wild-type DENV-2 virus. The linear dipeptide compound 1 and the non-peptidic fused ring compound 2 show comparable activities against DENV-2 NS2B-NS3 protease and wild-type DENV-2 virus in a viral replication assay. The preliminary SAR reveals that a substituent and its stereochemistry at C-3 position, substitution (X) at N-2 arene and a linker (Y) between C-3 position and its attached arene are important for the fused-ring scaffold of pyrrolidino [1,2-c]imidazolidinone to block the active site of NS2B-NS3 protease. This promising structural core will facilitate the discovery of non-peptidic, potent NS2B-NS3 protease inhibitors to stop dengue virus infections.
Published online: 21 September 2016
Gesehen am 29.08.2018